1996
DOI: 10.1002/jbmr.5650110414
|View full text |Cite
|
Sign up to set email alerts
|

The heritability of bone mineral density, ultrasound of the calcaneus and hip axis length: A study of postmenopausal twins

Abstract: Population based studies have demonstrated that having a first degree relative with a hip fracture is predictive of future hip fractures. Postmenopausal bone mineral density (BMD), ultrasound of calcaneus and hip axis length are associated with hip fracture, with the association for ultrasound and hip axis length being independent of BMD. The aim of this study was to determine the genetic component of these three important risk factors. We performed a classical twin study using 500 normal female twins, 128 ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
2
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(125 citation statements)
references
References 15 publications
4
116
2
3
Order By: Relevance
“…A number of candidate genes have already been identified including those that code for the following; vitamin D receptor (VDR), oestrogen receptor, insulin growth factor, parathyroid hormone and type I collagen. Twin studies have been widely used to assess the importance of genotype in the osteoporotic condition, finding that between 60% and 85% of BMD variance is genetically determined [31,32]. Research has also been conducted on non-BMD risk factors; Mann et al investigated the genetic influence on non-BMD CRFs including body mass index (BMI), age at menopause and smoking history.…”
Section: Genomic Markersmentioning
confidence: 99%
“…A number of candidate genes have already been identified including those that code for the following; vitamin D receptor (VDR), oestrogen receptor, insulin growth factor, parathyroid hormone and type I collagen. Twin studies have been widely used to assess the importance of genotype in the osteoporotic condition, finding that between 60% and 85% of BMD variance is genetically determined [31,32]. Research has also been conducted on non-BMD risk factors; Mann et al investigated the genetic influence on non-BMD CRFs including body mass index (BMI), age at menopause and smoking history.…”
Section: Genomic Markersmentioning
confidence: 99%
“…Twin studies, as powerful designs to study genetic epidemiology of aging-related traits, have confirmed the significant influence of genetic factors on bone mineral density (BMD). (3)(4)(5) However, it is difficult to interpret the genetic effects on bone loss from these studies because these cross-sectional studies more reflect variations in peak bone mass rather than bone loss. Previous longitudinal studies were underpowered due to small sample size (6)(7)(8) or young age range of participants.…”
Section: Introductionmentioning
confidence: 99%
“…The CSMI estimated with DXA has been found to be highly correlated with the CSMI measured directly on cadaver specimens (r 2 =0.96) [26]. The automatic identification of the weakest cross-section of the femoral neck is the central part of the hip strength analysis software and this cross-section level is then used for the subsequent calculations of section modulus (SM, cm 3 ) and the femoral neck width (FN width, cm). The section modulus is also an estimate of the ability of the femoral neck to withstand bending forces, and is calculated as CSMI divided by the distance from the center of the mass to the superior neck margin.…”
Section: Bone Mineral Density and Hip Structure Analysismentioning
confidence: 96%
“…Bone strength is determined by a combination of genetic and environmental factors. Family and twin studies have shown a significant heritable component, accountable for up to 80% with both BMD and femoral structure [3][4], between 51% and 79% for hip axis length [5] and from 60%-80% for the other aspects of bone geometry as well as bone quality [3,[6][7]. Data modelled in twins indicates that both specific and shared genetic factors act on individual bone phenotypes [8][9] and may explain the partially BMD-independent associations often observed with fracture [10][11].…”
Section: Introductionmentioning
confidence: 99%